2021
DOI: 10.3390/plants10081515
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Alterations in Cells of Sunflower Linear Glandular Trichomes during Maturation

Abstract: Sunflower and related taxa are known to possess a characteristic type of multicellular uniseriate trichome which produces sesquiterpenes and flavonoids of yet unknown function for this plant. Contrary to the metabolic profile, the cytological development and ultrastructural rearrangements during the biosynthetic activity of the trichome have not been studied in detail so far. Light, fluorescence and transmission electron microscopy were employed to investigate the functional structure of different trichome cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Early studies indicated that the synthesis and accumulation of secretions are followed by degeneration and autolysis in the secretory cells, including the autolysis of glandular cells, nuclear disorganization, cytoplasmic condensation, and the disruption of endoplasmic reticulum (ER) cisternae and multivesicular bodies [ 2 , 3 , 4 , 5 , 6 , 7 ]. Amrehn and Spring [ 8 ] reported that the deposition of fluorescent and brownish metabolites in the mature secretory cells of sunflower linear glandular trichomes is associated with the disintegration of their subcellular compartments. Recently, a comparative proteomic analysis of latex from Euphorbia kansui laticifers at different developmental stages was studied by Zhao et al [ 9 ], and the result showed that partial cytoplasmic degradation is positively correlated with secondary metabolite synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies indicated that the synthesis and accumulation of secretions are followed by degeneration and autolysis in the secretory cells, including the autolysis of glandular cells, nuclear disorganization, cytoplasmic condensation, and the disruption of endoplasmic reticulum (ER) cisternae and multivesicular bodies [ 2 , 3 , 4 , 5 , 6 , 7 ]. Amrehn and Spring [ 8 ] reported that the deposition of fluorescent and brownish metabolites in the mature secretory cells of sunflower linear glandular trichomes is associated with the disintegration of their subcellular compartments. Recently, a comparative proteomic analysis of latex from Euphorbia kansui laticifers at different developmental stages was studied by Zhao et al [ 9 ], and the result showed that partial cytoplasmic degradation is positively correlated with secondary metabolite synthesis.…”
Section: Introductionmentioning
confidence: 99%